1994
DOI: 10.1152/jn.1994.71.2.821
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition in human extrastriate cortex

Abstract: 1. Twenty-four patients with electrodes chronically implanted on the surface of extrastriate visual cortex viewed faces, equiluminant scrambled faces, cars, scrambled cars, and butterflies. 2. A surface-negative potential, N200, was evoked by faces but not by the other categories of stimuli. N200 was recorded only from small regions of the left and right fusiform and inferior temporal gyri. Electrical stimulation of the same region frequently produced a temporary inability to name familiar faces. 3. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
287
3
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(334 citation statements)
references
References 0 publications
41
287
3
1
Order By: Relevance
“…The previous studies demonstrated that the capability to discriminate faces from other objects is not affected in temporal lobe lesions, supporting the thesis that such processing is done in the ventral temporal-occipital areas (Allison et al, 1994;Haxby et al, 1996;Kanwisher et al, 1997;Steeves et al, 2006;Pitcher et al, 2007). The neuropsychological tests presently available have nevertheless been unable to detect reliably abnormalities in face recognition (Duchaine and Weidenfeld, 2003;Duchaine and Nakayama, 2004), making it difficult to produce strong inferences about the localizations of occipital lesions from the obtained results.…”
Section: Introductionmentioning
confidence: 81%
“…The previous studies demonstrated that the capability to discriminate faces from other objects is not affected in temporal lobe lesions, supporting the thesis that such processing is done in the ventral temporal-occipital areas (Allison et al, 1994;Haxby et al, 1996;Kanwisher et al, 1997;Steeves et al, 2006;Pitcher et al, 2007). The neuropsychological tests presently available have nevertheless been unable to detect reliably abnormalities in face recognition (Duchaine and Weidenfeld, 2003;Duchaine and Nakayama, 2004), making it difficult to produce strong inferences about the localizations of occipital lesions from the obtained results.…”
Section: Introductionmentioning
confidence: 81%
“…Allison and co-workers studied neurophysiological correlates of face perception in 98 epileptic patients using subdural recordings over the extrastriate cortex (15,16). Unknown faces, front views of cars, scrambled faces, and scrambled cars were used as visual stimuli.…”
Section: Category-related Processing: Faces Versus Nonface Stimulimentioning
confidence: 99%
“…Baron-Cohen (1995) proposed that gaze detection is governed by a cognitive module involving eye detection, gaze detection and determination of whether gaze makes direct contact. Lesion and functional brain studies in humans and primates support the role of the fusiform gyrus in face processing (Allison et al 1994, Clark et al 1996, Kanwisher et al 1997. Gaze detection consistently involves areas of the superior temporal sulcus (Perrett et al 1992, Campbell et al 1999, Hoffman and Haxby 2000, Pelphrey et al 2004 and prefrontal lobe (Wicker et al 1998), that are already implicated in schizophrenia, based on volumetric and functional studies (McCarley et al 1993, Gur and Pearlson 1993, Zipursky et al 1994.…”
Section: Introductionmentioning
confidence: 98%